TEACHER EDUCATION AND PROTECTION TO THE CHILD MEANING CONSTRUCTION - Helenise Sangoi Antunes (Travessias, 2009)
This article aims to investigate the possibilities that teacher education constitutes in atmosphere of speeches and referrals about the child situation in brazil. This study is qualitative; it uses bibliographic research and semi-structured interview with the participants. In this view, we observe that the teaching contents by teachers need to be revised because there is not syntony with the real life of brazilian child. The posture of teacher preparation programs studentson the knowledge needs be revised too. This epistemological posture on the knowledge makesteachers do not create the learning together the students, what constitutes an activity linked with students sociocultural reality, fundamental to educational demands. All these aspects are permeates by an important question: the professional linked with the personal. According to nvoa ( 1992: 17), a maneira como cada um de ns ensina est diretamente dependente daquilo que somos como pessoa quando exercemos o ensino. We believed that the reflection incorporation in teacher education process, the careful with teaching practice in classes, the constant searching by improvement, the own critics, and the capacity to think on new signification of knowledge permit the possibility of